The Liturgical Reform from 1963 until Today … and Beyond - Faggioli, Massimo (Toronto journal of theology, 2016)
The article recapitulates the importance of the constitution Sacrosanctum Concilium of Vatican ii and of the liturgical reform in terms of the constitution's overall contribution to the theology of Vatican ii, especially its ecclesiology. The article also draws a brief history of the reception and application of the liturgical reform after Vatican ii in a few phases, adding to the periodization proposed by Martin Klöckener: 1964-1968 (the foundations of the liturgical reform), 1968-1974 (edition of liturgical books), 1974-1988 (the beginning of an ambivalence of the papacy about the liturgical reform of Vatican ii), 1988-2000 (signs of centralization and coming back to Latinization), 2001-2005 (Liturgiam Authenticam, 2001), and the pontificate of Benedict xvi (especially the motu proprio Summorum Pontificum, 2007). An open issue is the contribution of Francis to this history of reception of the liturgical reform. The final part of the article explores how to move beyond a certain "Vatican ii nominalism" through a renewed look at the ecclesiology of the liturgical constitution, especially in light of the pontificate of Pope Francis and of the important contributions of the liturgical reform to the theological debate in these last fifty years.